Cerebello-brainstem dominant form of X-linked adrenoleukodystrophy with intrafamilial phenotypic variability - Choi, Jae-Hwan; Kim, Hyun Sung; Oh, Eun Hye; Lee, Jae Hyeok; Cheon, Chong Kun (Frontiers in Neurology, 2022)
X-linked adrenoleukodystrophy (X-ALD) is the most common peroxisomal disorder caused by mutations in the ATP-binding cassette subfamily D member 1 gene (ABCD1) of Xq28. Patients with ALD present various phenotypes depending on the tissues affected. Adrenomyeloneuropathy and childhood cerebral ALD are the most common phenotype, but there are several additional ALD phenotypes, including adult cerebral ALD, cerebello-brainstem dominant ALD, and isolated adrenocortical insufficiency. This study aimed to describe the clinical and radiological characteristics of a cerebello-brainstem dominant form of X-ALD. Three affected members from a family with cerebellar ataxia presented with slurred speech, ataxia, and spasticity, but showed obvious differences in phenotypic severity and radiological findings. The levels of very long-chain fatty acids were elevated in each member, while only one had adrenal dysfunction. Whole-exome sequencing identified a hemizygous missense mutation (c.887A>G, p.Tyr296Cys) of ABCD1 in all affected members, which is likely to destabilize the overall structure of the ABCD1 protein in protein structural modeling. We report a cerebello-dominant form of X-ALD caused by a missense variant in ABCD1. This report highlights intrafamilial phenotypic variability in X-ALD.